Web-based bilingual English and Mandarin dictionary for beginners / Vyonne Edwin - Edwin, Vyonne (2009)
The growing numbers of web-based dictionary websites that have been published online have broadened the approaching techniques in learning and understanding a new language. These kinds of websites can be used as teaching kit to support students in undertaking independent and self directed study. Although Mandarin language had became one of UiTM's additional third language subjects, there are still no additional online approach provided to be used for Mandarin lecturers to help students in independent and self directed study. Therefore this research is conducted to develop a Web-based Bilingual English and Mandarin Dictionary for Beginners to help lecturers in providing students with information regarding Mandarin language. The purpose of this research is to identify the requirements, design and to develop and also evaluate the prototype of web-based English to Mandarin and Mandarin to English dictionary. In conducting this research, questionnaire distribution, interviewing, journals and websites reading and studies on existing system are among the methods that are used. This Web-based Bilingual English and Mandarin Dictionary for Beginners will be beneficial to Mandarin lecturers in term of giving them the facility in maintaining and updating data faster and easier.